Analisis Kinerja Karyawan PT. BPR Syariah Gala Mitra Abadi Purwodadi Kab. Grobogan - Umni Atus Afifah; Efriyani Sumastuti; Ratih Hesty Utami (PT. PENERBIT TIGA MUTIARA, 2025)
An organization must effectively maximize and enhance employee performance to achieve its objectives. Based on an observation report from PT. BPR Syariah Gala Mitra Abadi, complaints have been raised regarding wage and compensation issues that do not meet expectations, leading to a decline in employee motivation. This study aims to analyze the impact of compensation, work motivation, job satisfaction, work discipline, and work environment on employee performance at PT. BPR Syariah Gala Mitra Abadi. The population of this study consists of 198 employees, with a sample size of 133. The data analysis methods used include instrument testing, descriptive statistics, classical assumption tests, and multiple regression analysis. The study's findings indicate that: 1) Compensation has a positive and significant effect on employee performance (t value 3.166, sig value 0.002). 2) Work motivation has a positive and significant effect on employee performance (t value 8.877, sig value 0.000). 3) Job satisfaction has a positive and significant effect on employee performance (t value 8.877, sig value 0.000). 4) Work discipline has a positive and significant effect on employee performance (t value 3.191, sig value 0.002). 5) The work environment has a positive and significant effect on employee performance (t value 2.085, sig value 0.032). 6) Collectively, these factors—compensation, work motivation, job satisfaction, work discipline, and work environment—have a positive and significant impact on employee performance (F value 67.787, sig value 0.000). This study highlights the importance of managing these factors to improve employee performance at PT. BPR Syariah Gala Mitra Abadi.